Implantation and annealing studies of Tm-implanted GaN - Lorenz, K.
Thulium ions were implanted into metal organic chemical vapour deposition (MOCVD) grown GaN films with different fluences at implantation temperatures of 20, 400 and 500°C. Subsequent annealing of the samples was performed in a rapid thermal annealing apparatus. The lattice damage introduced by the implantation and the effect of post-implant annealing were investigated with the Rutherford backscattering (RBS)/channelling technique. We observe that implantation at 500°C considerably reduces the induced lattice damage and increases the amorphisation threshold. The lattice-site location of the implanted ions was determined by performing detailed channelling measurements for the 〈0001〉 and 〈101̄1〉 crystal directions. The results show that Tm ions mainly occupy substitutional Ga-sites directly after implantation and after annealing. The optical properties of the ion-implanted GaN films have been studied by room temperature cathodoluminescence (CL) measurements. Well-defined emission due to intra-4f shell transitions of the Tm3+ ions are observed in the blue spectral range at 477nm and in the near infra-red (IR) at 804nm